Tuva tourist: linguistic and cultural features of marketing Internet communication - Sknarev, Dmitry S.; Rusakova, Mavzhida M.; Nelyubova, Natalia Yu. (The New Research of Tuva, 2023)
The article critically examines the issue of linguacultural specificity within the domain of marketing internet communication, focusing on materials sourced from Russian-language websites and the YouTube video hosting platform dedicated to tourism in the Republic of Tuva. The study delineates how the regional culture intricately shapes the selection of linguistic tools for crafting a compelling Tuva brand tailored for potential audiences in online promotional endeavors. Various linguistic constructs actively contribute to the representation of the Tuva brand, with particular emphasis placed on the efficacy of epithets and phraseological units. Tuva is portrayed as a distinctive tourist brand, characterized as a “unique land”, a “land of contrasts”, a “place of power”, a “land of living traditions”, among other epithets. Special attention is directed towards the portrayal of Kyzyl, the regional capital, which is depicted based on local landmarks (Cechenling Temple, the Center of Asia obelisk, the Aldan-Maadyr National Museum, etc.), hospitality establishments (hotels), and indigenous souvenirs encompassing elements of the Tuvan costume, utensils, home goods, and smoking pipes. Noteworthy is the development of proprietary brands in Tuva, such as the “Devig” clothing brand, the “Vaviol” company (“Herbs of Tuva”), Brand Dongak, and others. The Tuvinian national cuisine is also a focal point, with frequent references in online communication to gastronomic brands in the region bearing Tuvan names: suttug shai, khymys, araga, buuza, khuzhur, manchyyr, and others. The linguacultural specificity of tourism websites in the Republic of Tuva lies in the presentation of a unique regional image that encapsulates information on diverse forms of tourism, including spiritual, sports, health-oriented, ecological, cultural-cognitive, and more. This multifaceted representation is conveyed through specific figurative linguistic means, notably tropes and phraseological units. Depending on the chosen destination, each traveler has the opportunity to explore the natural landscape diversity of the region and gain an appreciation for the unique authenticity of its culture.